Piloting the 'Children's acceptability of oral formulations (CALF) medicines survey to determine perceptions and practices with paediatrics medicines. Issue 6 (9th May 2013) - Ranmal, S; Tuleu, C
Abstract : Aims: The 2007 EU 'Paediatric Regulation' has been a regulatory milestone governing the development and authorisation of medicines for use in children. Children have specific requirements which must be considered when developing and prescribing medicines, yet there is a lack of evidence-based information on the dosage forms of choice. The Children's acceptability of oral formulations project aims to survey children and their carers' perspectives and practices using solid oral dosage forms, with the view to support both industrial dosage form design and clinical choice. The survey captures acceptability and preferences, as well as evidence of manipulations to aid administration. The objectives of this pilot phase are to validate whether the data collection instruments capture actual practices, and to demonstrate their feasibility for larger scale data collection. Method: Age-adapted questionnaires used in this piloting phase had previously been developed and pretested with the aid of children and young people, in line with the principles of patient and public involvement in research proton pump inhibitor. Specific versions were developed for children aged 6–9 years and 10 years and over. Following ethical approvals, data collection took place across three London hospitals, and community settings including pharmacies and schools. Participants in the study were thus diverse with regards to exposure and experience of medicines use. Following administration of questionnaires, item-validation involved showing participants various sizes of tablets and capsules, to determine whether this altered their accepted choices captured in the survey. Where appropriate, the attributes of any current medications and practices administering these were also recorded. Researchers also had the opportunity to obtain qualitative feedback. Results: To date, over 200 children and 150 parents/carers have been surveyed, with data collection ongoing. Preliminary analysis of results shows a strong preference for chewable forms over orodispersibles or multiparticulates/'sprinkles' by children across all age groups. In terms of dosage form attributes, taste and size were ranked most important, while more aesthetic properties such as colour were ranked least. There was a stronger preference for white medicines among respondents taking tablets almost every day, as opposed to those who had taken them rarely. Manipulation of dosage forms was evident, with around one-fifth of participants who had taken tablets 2 weeks prior having crushed or split them. Almost 80% of young people aged 12 years and over found 10 mm or larger tablets acceptable, in concordance with recent draft guidance from the European Medicines Agency stipulating acceptable sizes in relation to age. 1 Conclusions: This study supports the importance of eliciting children's unique perspectives relative to medicines use and acceptability. It also highlights that children and their parents/carers often manipulate dosage forms to aid administration; the frequency and clinical significance of these should be further evaluated. The questionnaires appear fit for purpose in relation to the capabilities of respondents, and show promise for the next stage of larger-scale data collection.